1971
DOI: 10.1126/science.172.3986.955
|View full text |Cite
|
Sign up to set email alerts
|

DDE Residues and Eggshell Changes in Alaskan Falcons and Hawks

Abstract: Eggshell thickness after exposure to DDT was reduced by 21.7 percent in Alaskan tundra peregrines, by 16.8 percent in taiga peregrines, by 7.5 percent in Aleutian peregrines, by 3.3 percent in rough-legged hawks, and not at all in gyrfalcons. Tundra peregrine eggs contain an average of 889 parts of DDE per million (lipid basis); taiga peregrine eggs contain 673 parts per million; Aleutian peregrine eggs contain 167 parts per million; rough-legged hawk eggs contain 22.5 parts per million; and gyrfalcon eggs con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
2
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(85 citation statements)
references
References 14 publications
4
78
2
1
Order By: Relevance
“…Some of the first studies documenting the decline of peregrine falcons, eggshell thinning, and its relationship to DDE were in the northern populations of Alaska and Canada (Cade et al, 1968(Cade et al, , 1971Berger et al, 1970;Fyfe et al, 1976). Alaskan arctic falcon populations experienced a significant decline (Cade et al, 1971), but are currently experiencing a population recovery (Kiff, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the first studies documenting the decline of peregrine falcons, eggshell thinning, and its relationship to DDE were in the northern populations of Alaska and Canada (Cade et al, 1968(Cade et al, , 1971Berger et al, 1970;Fyfe et al, 1976). Alaskan arctic falcon populations experienced a significant decline (Cade et al, 1971), but are currently experiencing a population recovery (Kiff, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Alaskan arctic falcon populations experienced a significant decline (Cade et al, 1971), but are currently experiencing a population recovery (Kiff, 1988). The reports of the decline of Alaskan and Canadian peregrines provided an impetus to study falcon populations, eggshell thinning, and pollutants in other northern areas such as Norway (Nygård, 1983), Finland (Lindén et al, 1984, and Greenland (Walker et al, 1973;Burnham and Mattox, 1984;Springer et al, 1986;Mattox and Seegar, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe and North America during the 1950s and 1960s, populations of many raptors, which are at the top of food chains, were affected by persistent and bioaccumulable organochlorine insecticides, especially 1,1-dichloro-2,2-bis(pchlorophenyl)ethylene (DDE), a metabolite of 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (DDT) (Ratcliffe, 1967(Ratcliffe, , 1970Cade et al, 1971;Newton and Bogan, 1978). After a ban on most organochlorine insecticides in the 1970s, organophosphorus (OP) and carbamate (CB) insecticides became the most widely used classes of insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Bell (1972) (Cade, et al, 1971). We have observed that in some raptors with thinned eggshells, the weight of the incubating female has caused egg breakage.…”
Section: -5 Per Panementioning
confidence: 91%